Homoeopathic Treatment of Lichen Simplex Chronicus: A Case Report (Advancements in Homeopathic Research, 2023)
Lichen simplex chronicus (LSC) or neurodermatitis  is a chronic type of skin disease which features itself  as chronic localized and lichenified form of atopic  dermatitis. Conventional treatment only keeps the  symptoms in abeyance and eruptions reappear again  and again. Here a case of LSC, of 60 year old male with  a history of one and half year old dry, papular lesions  presented. On the basis of the totality of symptoms,  Homoeopathic medicine Sepia succus 200C was  prescribed and gradually the patient showed stable  improvement in signs and symptoms and reached  remission by the end of 4 months. There was no  recurrence over the next 8 months. Causal attribution  of changes in his condition to the Homoeopathic  treatment was depicted by modified Naranjo criteria  (MONARCH). This case report evidently suggests  that Homoeopathy can serve as a possible treatment  option for the management of neurodermatitis cases.
Keywords: Lichen Simplex Chronicus; Homoeopa thy; Sepia succus; case report; MONARCH